2018
DOI: 10.1080/17408989.2018.1485141
|View full text |Cite
|
Sign up to set email alerts
|

Teachers as frontline agents of integration: Finnish physical education students’ reflections on intercultural encounters

Abstract: The responsibilities of physical education teachers are responding to increased migration and wider political shifts in Europe. How might tertiary institutions prepare the next generation of PE teachers to address issues of social inclusion and cultural pluralism? This article critically reflects on an experiential learning intervention in Jyväskylä, Finland, in which trainee PE teachers facilitated kinaesthetic language-learning workshops for asylum seekers. We focus on how this intervention may have transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 29 publications
0
19
0
4
Order By: Relevance
“…Consequently, 'teachers are still struggling to find ways to implement culturally responsive pedagogy into their physical education classes to meet the needs of diverse learners' (Columna, Foley, & Lytle, 2010, p. 309). Thus, some scholars advocate the need for physical education teacher education (PETE) students to develop their intercultural sensitivity in their preparation for future encounters with pupils from different cultures (Anttila, Siljamäki, & Rowe, 2018;Burden, Hodge, O'Bryant, & Harrison, 2004;Grimminger, 2008Grimminger, , 2011Grimminger-Seidensticker & Möhwald, 2017).…”
Section: Zooming In On Pementioning
confidence: 99%
“…Consequently, 'teachers are still struggling to find ways to implement culturally responsive pedagogy into their physical education classes to meet the needs of diverse learners' (Columna, Foley, & Lytle, 2010, p. 309). Thus, some scholars advocate the need for physical education teacher education (PETE) students to develop their intercultural sensitivity in their preparation for future encounters with pupils from different cultures (Anttila, Siljamäki, & Rowe, 2018;Burden, Hodge, O'Bryant, & Harrison, 2004;Grimminger, 2008Grimminger, , 2011Grimminger-Seidensticker & Möhwald, 2017).…”
Section: Zooming In On Pementioning
confidence: 99%
“…That ethnicity appears to be absent from the girls' PE experiences might be a sign that ethnic, cultural, or religious identities are not considered important in PE; hence, they are neither recognized as a recourse (Thorjussen and Sisjord, 2020) nor viewed in terms of how they might create lines of exclusion or tension among students of diverse backgrounds (Thorjussen and Sisjord, 2018). This interpretation reflects that PE is taken for granted as an arena for social inclusion and integration in diverse societies (Anttila et al, 2018;Barker et al, 2017;Goodyear et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, research has indicated that PE's perceived role in social inclusion in increasingly diverse societies is taken for granted (Anttila et al, 2018;Barker et al, 2017;Goodyear et al, 2014). Yet, studies have indicated that social relations in PE are formed by hierarchical power relations, positioning students based on their gender, ethnicity, race, social class, and other markers of difference (Hill and Azzarito, 2012;Hills, 2007Hills, , 2010With-Nielsen and Pfister, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, PE teachers have a special opportunity to support students from refugee backgrounds in discovering their sport-related interests and to encourage them to deepen these interests beyond school, in line with PE curricula that formulate the goal of lifelong physical activity and health (Conference of Ministers of Education Cultural Affairs, 2005 ). However, this can only succeed if PE teachers, who are usually part of the majority culture and thus occupy privileged social positions (Anttila et al, 2018 ), meet students from refugee backgrounds without prejudice and give them the opportunity to develop freely. Such an unbiased encounter can be hindered by the likelihood that many students from refugee backgrounds have little experience with sports, are not familiar with Western sports culture, or have not received any education in sports in their home country (Doherty and Taylor, 2007 ).…”
Section: Introductionmentioning
confidence: 99%